2018
DOI: 10.1007/s13353-018-0463-4
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillar myopathy in the genomic context

Abstract: Myofibrillar myopathy (MFM) is a group of inherited muscular disorders characterized by myofibril dissolution and abnormal accumulation of degradation products. The diagnosis of muscular disorders based on clinical presentation is difficult due to phenotypic heterogeneity and overlapping symptoms. In addition, precise diagnosis does not always explain the disease etiopathology or the highly variable clinical course even among patients diagnosed with the same type of myopathy. The advent of high-throughput next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 66 publications
0
58
0
2
Order By: Relevance
“…These include repeat expansion diseases, copy number variants and deep intronic mutations [21]. Oligogenic inheritance has also been speculated as a potential pathogenic mechanism [22] but this has not been explored in this study.…”
Section: Ttn Gene Variants Accounted For the Largest Single Group Of mentioning
confidence: 98%
“…These include repeat expansion diseases, copy number variants and deep intronic mutations [21]. Oligogenic inheritance has also been speculated as a potential pathogenic mechanism [22] but this has not been explored in this study.…”
Section: Ttn Gene Variants Accounted For the Largest Single Group Of mentioning
confidence: 98%
“…Common proteins present in these aggregates include Filamin C (FILC), αB-crystallin (CRYAB), BAG3, and Desmin (DES), among others. The inability of MFM patients to clear these aggregates results in myofibrillar degeneration and a decline in muscle function [74][75][76][77][78][79][80]. Interestingly, mutations in Drosophila NUAK phenocopy both structural and functional deficits observed in MFM patients, including Fil and CryAB accumulation, muscle degeneration, and locomotor defects.…”
Section: Connections To Protein Aggregation Diseasementioning
confidence: 99%
“…Clinical significance of these additional variants remains speculative and needs to be elucidated; they might contribute to the variability of the phenotype due to a synergistic or an antagonistic effect [43]. Alternatively, it has been suggested that the cumulative burden of variants might affect the functioning of target tissue modulating the penetrance and/or the expression of clinical phenotype [5].…”
Section: Discussionmentioning
confidence: 99%
“…MFM are usually transmitted as an autosomal dominant trait; however, X-linked, autosomal recessive and sporadic cases have been described [1][2][3][4]. Causative mutations have been identified in a minority of patients in one of the following genes: desmin (DES), αBcrystallin (CRYAB), myotilin (MYOT), Z-band alternatively spliced PDZ-containing protein (LBD3/ZASP), Bcl2-associated athanogene-3 (BAG3), and filamin C (FLNC) [1][2][3][4][5]. Recent mutations in FHL1, TTN, DNAJB6, PLEC, ACTA1, HSPB8, LMNA, KY, PYROXD1, and SQSTM1 have also been reported in patients featuring MFM pathology highlighting the variability and complexity of these muscular disorders [5].…”
Section: Introductionmentioning
confidence: 99%